Rincones de juego-trabajo y su relación con el desarrollo de habilidades sociales en los niños y niñas de 4 años de edad del nivel inicial ii del centro de desarrollo infantil bilingüe “ carita de ángel ”, de la ciudad de Quito. Período lectivo 2014-2015 - Maldonado Castro, María Teresa (2015)
The present research work has as main purpose, a study on, CORNERS OF PLAY-WORK AND ITS RELATIONSHIP WITH THE DEVELOPMENT OF SOCIAL SKILLS IN CHILDREN OF 4 YEARS OF AGE OF INITIAL LEVEL II CHILD DEVELOPMENT CENTER BILINGUAL "Baby Face" CITY OF QUITO. LECTIVO PERIOD 2014-2015. This structured around graduation guidelines in force at the National University of Loja. The central problem of the research was to determine that Way Corners Game - Work related to the Development of Social Skills. General objective was to determine Corners Play-Work and its relationship with the Development of Social Skills children 4 years of age Initial Level II Bilingual Child Development Center " Carita de Ángel" was proposed , of the city of Quito. Lectivo 2014-2015. " The methods used were: Scientist, Description, Model Analytic-Synthetic, and Statistical Method. The techniques and instruments applied were: The Survey conducted and directed to teachers of Bilingual Child Development Center "Carita de Angel" to establish Corners Play-Labour used in the daily work, and Questionnaire Social Skills aimed at children aged 4 Initial Level II Bilingual child Development Center "Carita de Ángel" to evaluate Social Skills thereof. The methodology followed was adequate; methods and techniques, was a powerful auxiliary to achieve the expected results and objectives. Application of the Survey was reached to verify and establish that 100% of the teachers have selected the Corner Logical-mathematical, working methodology in their workday. According to the results of applying Questionnaire Social Skills, the following averages were obtained: 46% of children If they have developed their social skills, 13% NO 29% SOMETIMES and 12% corresponds to NO OBSERVABLE group.